Kitchen renovation works / Nur Azlina Azizan - Azizan, Nur Azlina (Universiti Teknologi MARA UiTM,Perak, 2022)
This report briefly describe the process of kitchen renovation works and the problem occur during the kitchen renovation works. The objective of this report is to identify the process of kitchen renovation works investigate the problems in kitchen renovation works and also identify the suitable design of kitchen.. In this report there are two method of study that is primary and secondary to obtain information on kitchen renovation works, problems occur and suitable design for kitchen. Observation has been made by site visit to the project site. In addition, for the interview, interviewed a person who experienced in the work of kitchen renovation works such as site supervisor and project manager. The finding from this report is kitchen renovation works start from excavating soil, installation of reinforcement,formwork,and plumbing, brick binding and plastering, and worktop making and installation.